Metastatic cutaneous deposits as the initial feature of rectal adenocarcinoma. Issue 1 (February 2020) - Sadler, Katie A; Baxter, MA; Peters, AL; Grose, D
Cutaneous metastases in colorectal cancer are rare, occurring in less than 6% of cases. They usually present after diagnosis of a primary tumour and are typically associated with disseminated disease and a poor prognosis. We present an unusual case of a 71-year-old female in whom cutaneous metastases were the initial feature of an underlying colorectal cancer.